The cost of an outbreak of Aujeszky disease - Protas, José Fernando da Silva; Sobestiansky, Jurij; Soncini, Ricardo (Pesquisa Agropecuaria Brasileira, 2014)
An evaluation of the economic efficiency of a growing-finishing pig farm, under an acute outbreak of the Aujeszky Disease (AD), which occured in Santa Catarina State, south of Brazil, from November 1983 to march, 1984, was made. The only treatment aiming at the control of the outbreak was a shoting of one inactivated vaccine with oil acting as adjuvant. The total control of the outbreak after five months, with important decreases in the losses after the third month, suggests that the treatment has been efficient in the control and prevention of the AD losses caused by the disease were equivalent to the loss of 124,766 kg of swine live weight or nearly 3% of the total annual income of the studied pig farm.